Titanium dioxide (TiO 2) nanopowder prepared by the low temperature solvothermal method - Pookmanee P. (2014)
Titanium dioxide (TiO2) nanopowder was prepared by the low temperature solvothermal method with starting chemicals containing titanium isopropoxide (Ti(OCH(CH3)2)4), ammonium hydroxide (NH4OH), nitric acid (HNO3) and ethanol (C 2H5OH) in a PTFE-lined autoclave. The pH of the mixed final solution was 1 and treated at 100-200°C for 2-6 h. The white powder was filtered and dried in an oven at 80°C for 24 h. The phase transition was characterized by X-ray diffractometer (XRD). The morphology and microstructure were investigated by scanning electron microscope (SEM). The chemical composition was identified by energy dispersive X-ray spectrometer (EDXS). The surface area was determined by Brunauer, Emmett and Teller analyzer (BET). © 2013 Copyright Taylor and Francis Group, LLC.